IN VITRO ANTIFUNGAL ACTIVITY OF THYME OIL AGAINST CANDIDA ALBICANS ISOLATED FROM NAIL FUNGUS (ONYCHOMYCOSIS) - ALAHMAD, AYA; BERAKDAR, NOURA; RADWAN, ABDULKARIM; ALYOUSEF, ESRAA (Innovare Journal of Life Sciences, 2022)
Objectives: The aim of this study is to investigate the antifungal activity of thyme oil against Candida albicans of nail fungus (onychomycosis) from patients in Syria. Methods: An in vitro study was carried out using the following C. albicans strains involved in onychomycosis using well diffusion (WD) testing: C. albicans (ATCC 90028) and 15 strains were compiled from Aleppo Hospital. The antifungal activity of thyme oil was determined in the form of inhibition zone using antifungal assay agar WD testing. In all experiments, the obtained results indicated that thyme oil has inhibitory effects on C. albicans (ATCC 90028) and some 15 strains. Results: This study showed that thyme oil was active against the tested C. albicans strains. Thyme oil was more effective against C. albicans compared to terbinafine. thyme oil may have potential for use in the development of clinically useful antifungal preparations. Conclusion: Thyme oil might be highly effective in the natural prevention treatment of onychomycosis.